Antidiabetic Potential of Sophora Species: Mechanisms, Bioactive Constituents, and Therapeutic Prospects - Mousavi, Mahdis; Moridi Farimani, Mahdi; Kashfi, Khosrow; Ghasemi, Asghar (Planta Medica, 2025)
Diabetes is a major global health concern, and achieving optimal glycemic control remains a challenge for many patients. Despite the availability of current antidiabetic medications, about two-thirds of patients worldwide fail to achieve adequate glycemic control, underscoring the need for novel treatments. Herbal medicine has significantly contributed to drug discovery, and Sophora, a genus in the Fabaceae family, has long been used in traditional medicine. Preclinical studies suggest that various chemical constituents of Sophora exhibit antidiabetic properties. This review summarizes in vitro and in vivo evidence on the antidiabetic effects of Sophora, highlighting its active ingredients and mechanisms of action. A literature search was conducted using Web of Science, Scopus, PubMed, and Google Scholar with the keywords ‘Sophora’, ‘diabetes’, and ‘herbal medicine’. Studies indicate that Sophora reduces fasting glucose in type 1 and type 2 diabetes (T2D) by approximately 33% and 37%, respectively. Additionally, it decreases body weight, improves glucose tolerance, reduces insulin resistance, and enhances lipid profiles in T2D. The antidiabetic mechanisms of Sophora involve the activation of phospholipase C-protein kinase C (PLC-PKC), phosphatidylinositol-3-kinase (PI3K)-Akt (PI3K-Akt), and adenosine monophosphate (AMP)-activated protein kinase (AMPK) pathways, leading to enhanced glucose uptake in the skeletal muscle. Furthermore, Sophora activates the PI3K-Akt pathway and inhibits nuclear factor-kappa B (NFκB), thereby reducing hepatic gluconeogenesis and inflammation. Among its active constituents, flavonoids exhibit the most significant antidiabetic activity. While Sophora holds promise for antidiabetic drug development, further preclinical studies assessing sex differences and long-term safety are required before progressing to human clinical trials.
Keywords: Sophora; herbal medicine; type 1 diabetes; type 2 diabetes; Fabaceae